Solution sets for differential equations and inclusions - Djebali, Smaïl; Górniewicz, Lech; Ouahab, Abdelghani (De Gruyter series in nonlinear analysis and applications ;, 2013)
"This monograph gives a systematic presentation of classical and recent results obtained in the last couple of years. It comprehensively describes the methods concerning the topological structure of fixed point sets and solution sets for differential equations and inclusions. Many of the basic techniques and results recently developed about this theory are presented, as well as the literature that is disseminated and scattered in several papers of pioneering researchers who developed the functional analytic framework of this field over the past few decades. Several examples of applications relating to initial and boundary value problems are discussed in detail."--Publisher's website.